Penerapan Multimetode Dalam Meningkatkan Kemampuan Membaca Dan Menulis Al-Quran Di Rumah Tahfidz Mihrobul Qur’an Perbaungan - Putra Ariadi; Alimuddin Siregar; Nurul Hidayah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the application of multiple teaching methods (multimethod approach) in improving students’ ability to read and write the Qur'an at Rumah Tahfidz Mihrobul Qur’an Perbaungan. The research employed a qualitative descriptive approach, using observation, interviews, and documentation as data collection techniques. The subjects of this study were Qur’anic teachers and students at the tahfidz house. The findings reveal that the use of varied methods—such as talaqqi (direct recitation), tikrar (repetition), writing verses, audio-visual aids, and educational games—significantly enhances students’ abilities to read and write the Qur’an. These methods accommodate different learning styles and developmental stages of the students. Moreover, the implementation of these methods also builds emotional and spiritual connections with the Qur’an, as reflected in students' daily habits and attitudes. In conclusion, the multimethod approach not only improves technical skills in Qur'anic literacy but also fosters a stronger love and appreciation for the Qur'an. Therefore, this approach is considered effective and recommended for broader use in non-formal Islamic educational institutions.